Robust and versatile assembly for emitter positioning, observation, and heating in atmospheric pressure field desorption mass spectrometry - Schweinfurth, Jan; Linden, H. Bernhard; Gross, Jürgen H. (European journal of mass spectrometry, 2024)
Atmospheric pressure field desorption (APFD) mass spectrometry (MS) has recently been introduced as a new variant of field desorption (FD) mass spectrometry. The development aimed at providing the basic characteristics of FD-MS in combination with instruments equipped with an atmospheric pressure (AP) interface. Hitherto, APFD has been demonstrated to yield both positive and negative even electron ions of highly polar or ionic compounds as well as to enable the generation of positive molecular ions, M+•, of polycyclic aromatic compounds. The prototype setup for APFD was based on a nano-electrospray ionization (nanoESI) source slightly modified to allow for emitter positioning in front of the AP interface of a Fourier transform-ion cyclotron resonance (FT-ICR) mass spectrometer. The entrance electrode of the interface was set to negative or positive high voltage with respect to the emitter at ground potential, thereby permitting the formation of positive or negative ions, respectively. This work describes a custom-built device for quicker and more reproducible sample loading on and positioning of field emitters at the entrance electrode of the atmospheric pressure interface of a mass spectrometer. In addition, the device provides means for observation of the emitter during operation and for resistive emitter heating as employed in traditional FD-MS. Emitter heating both speeds up the desorption of the analytes and allows for the desorption/ionization of analytes of higher molecular weight than without emitter heating. In some cases, the signal-to-noise ratio of APFD mass spectra is improved due to higher ion currents effected by compressing the entire process into shorter periods of spectral acquisition. The new setup enables robust and reliable operation in APFD-MS. Moreover, it has been designed as to allow for use on a range of instruments as it can either be used on an FT-ICR mass spectrometer or in combination with a trapped ion mobility-quadrupole-time-of-flight (TIMS-Q-TOF) instrument.